International Symposium on Gravity, Geoid and Height Systems 2016 : proceedings organized by IAG Commission 2 and the International Gravity Field Service, Thessaloniki, Greece, September 19-23, 2016 /: proceedings organized by IAG Commission 2 and the International Gravity Field Service, Thessaloniki, Greece, September 19-23, 2016. ([2019]) - Unknown
No abstract available